1998
DOI: 10.1007/s003830050234
|View full text |Cite
|
Sign up to set email alerts
|

Is a normally functioning gastrointestinal tract necessary for normal growth in late gestation?

Abstract: It is known that neonates with congenital abnormalities of the intestine tend to be growth-retarded. We wished to explore the hypothesis that normal fetal gut function is needed for normal growth in late gestation. If this is true, then different populations of babies with different congenital gut abnormalities would be expected to have similar impairments of growth and be small at birth. This growth retardation would be more marked in term than in preterm babies and would be independent of other congenital an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 21 publications
0
16
0
1
Order By: Relevance
“…Nonetheless, because of increased size of the small intestine with increasing fetal age, the total small intestinal OAT enzymatic activity of the fetus steadily increases with fetal age. It has been suggested that the small intestine of fetal humans and rabbits is an important source of enteral nutrition for somatic growth and development (22,23). The fetal porcine small intestine may play a similar role, and this may be especially important at d 60 and thereafter, when the intestinal epithelium possesses absorptive and digestive capacities greater than those at earlier stages of gestation (24,25) and is able to absorb amino acids from swallowed amniotic fluid.…”
Section: Oat In Fetal Pig Small Intestinementioning
confidence: 99%
“…Nonetheless, because of increased size of the small intestine with increasing fetal age, the total small intestinal OAT enzymatic activity of the fetus steadily increases with fetal age. It has been suggested that the small intestine of fetal humans and rabbits is an important source of enteral nutrition for somatic growth and development (22,23). The fetal porcine small intestine may play a similar role, and this may be especially important at d 60 and thereafter, when the intestinal epithelium possesses absorptive and digestive capacities greater than those at earlier stages of gestation (24,25) and is able to absorb amino acids from swallowed amniotic fluid.…”
Section: Oat In Fetal Pig Small Intestinementioning
confidence: 99%
“…Babies with upper gut atresias are at high risk of being born small for gestational age (Cozzi & Wilkinson 1969, Jolleys 1981, Pierro et al 1987. Babies with congenital gut anomalies are also proportionately smaller if they are born at term than if they are born preterm (Gitlin et al 1972, Pierro et al 1987, Blakelock et al 1998.…”
Section: Introductionmentioning
confidence: 99%
“…During the last trimester human fetuses swallow fluid (up to 750 mL d Ϫ1 ) that contains dilute concentrations of protein, free amino acids, and a variety of growth factors (5-7) derived from amniotic fluid and lung and nasal secretions. Although nutrients absorbed from these fluids are estimated to provide 10 -15% of fetal nitrogen requirements (8), and congenital intestinal atresia in humans is associated with fetal growthretardation (9,10), it remains unclear whether the swallowed fluid is particularly important for the final phases of fetal GIT development. Evidence from humans and experimental animals (sheep, rabbits) suggests that esophageal obstruction may impair growth of the intestine, particularly if obstruction is complete and prevents luminal input in the final stage of gestation (9 -17).…”
mentioning
confidence: 99%